Blockchain as the Database Engine in the Accounting System. Issue 2 (15th May 2019) - Tan, Boon Seng; Low, Kin Yew
Abstract: This paper examines the prediction that blockchain technology will transform accounting and the profession because transactions recorded on a blockchain can be aggregated into financial statements and confirmed as true and accurate. We argue that blockchain technology affects the database engine of the accounting information system (AIS) through digitisation of the current paper‐based validation process. In a blockchain‐based AIS, accountants will no longer be the central authority but will remain the preparer of financial reports required by regulations; they will continue to influence policies such as the choice and accreditation of validators and serve as validators of last resort. Audit evidence still needs to be gathered for rendering of an audit opinion in a blockchain‐based AIS. While digitisation of the validation process reduces the error rate and lowers the cost of vouching and tracing, and immutability of blockchain data reduces the incentive and opportunities for fraud, a blockchain‐based AIS alone does not guarantee that financial reports are true and fair. Lower error rates and reduced incentives for accounting fraud in a blockchain‐based AIS are expected to improve audit quality. This prediction will need to be empirically tested when blockchain‐based AIS become available. Using the three‐tier architecture of the AIS, this paper addresses the gap in the literature that misses how characteristics of blockchain technology can influence the implementation of a blockchain‐based AIS with related implications for the accounting profession. Abstract : This paper examines the prediction that blockchain technology will transform accounting and the profession because transactions recorded on a blockchain can be aggregated into financial statements and confirmed as true and accurate. Using the three‐tier architecture of the accounting information system, it addresses the gap in the literature that misses how characteristics of blockchain technology can influence the implementation of a blockchain‐based AIS with related implications for the accounting profession.